Researchers Probe Security Through Obscurity. - Edwards, Chris (Communications of the ACM, 2014)
The article focuses on the use of the obfuscation strategy to protect electronic data from computer hackers. Topics discussed include an attacker's inability to understand the code even if it is accessed, obfuscation techniques' reliance on heuristics, and the development of indistinguishability obfuscation (IO). Also mentioned are challenges associated with building a general-purpose theory of obfuscation, IO's power as a tool for designing cryptography, and the uses of other protocols such as functional encryption.